Crop diversification, sustainable production, and consumption (SDG-12) in rural Bangladesh: insights from the northern region of the country - Md. Mahbubur Rahman; Ashraful Islam; Shamshad Ferdousee (Circular Agricultural Systems)
The present study aimed to understand the current situation of diverse crop production in the northern region of Bangladesh. It also focused on sustainable production and consumption (SDG-12) and its association with crop diversification in the study area. The study adopted several tools and techniques of qualitative methods to design, collect data, and analyze them. By utilizing a non-random, purposive sampling, we chose some selected areas in northern Bangladesh, and following the sampling procedure, 50 farmers (small-scale agriculture producers) were selected to answer the central research questions and study-specific objectives. As part of the qualitative data analysis technique, this research employed a 'thematic analysis' tool to categorize the collected data under appropriate sub-themes which highlighted the study's major aims and objectives. It is demonstrated that crop diversification is one of the most important strategies for ensuring sustainable agriculture and production. In addition, diverse agricultural production plays a vital role in ensuring farmers' accessibility to food for household consumption. The study recommends that crop diversification should be thoroughly encouraged by the government of Bangladesh (GoB) to achieve SDG-12 (Sustainable Production and Consumption) by 2030. Additionally, the relevant officials of the GoB should provide necessary high-yielding seeds of diverse crops among the peasants in rural Bangladesh. Further research can be carried out on climate-resilient local food production systems to ensure sustainable food production and consumption in the country.